Penerapan Sanksi dalam Meminimalisir Kejahatan Anak Ditinjau dari Undang-undang Nomor 11 Tahun 2012 Tentang Sistem Peradilan Pidana Anak - Abnan Pancasilawati; Muhamad Noor (LP2M UIN Sultan Aji Muhammad Idris Samarinda, 2018)
The implementation of legislation either nationally or internationally linked to the implementation of restorative justice as one of the alterntif in the process of implementation of conviction against children in conflict with the law had been applied, but the case has not yet been thoroughly and still limited at the law enforcement officers and observers who are committed and integrity as well as having the attention to this problems. The implementation of restorative justice which is applied at each level of the process of criminal justice in the form of taking back the children to their parents, versioned by handing the children to Panti Sosial Marsudi Putra (PSMP), and the implementation of social integration through giving CB, CMB, and PB for children who are already serving imprisonment. Some obstacle factors the implementation of restorative justice as one of the alternatives in the implementation of conviction against children in conflict with the law, including physical building facilities and non-physical facilities and legal substance. It is because restorative justice has not been expressly regulated, even though in the law nomer 11, 2012 concerning about the Child Criminal System has been regulated but until now it has not been declared valid. The other factors are legal structure and legal culture.